The Influence of Work Motivation, Organizational Culture, and Work Discipline on PT Employee Performance. Pelindo Regional 2 Cirebon - Putri, Evila Yolanda; Putri, Amelia; Rahma, Aldilla; Susijawati, Noveria (Rescollacom (Research Collaborations Community), 2024)
This research aims to determine the influence of work motivation , organizational culture, and work discipline on the performance of PT employees. Regional Pelindo 2 Cirebon. This study uses a quantitative approach. The population in this research is employees of PT. Pelindo Regional 2 Cirebon consisted of 150 respondents and the sample used in this research was a saturated sample. Data were collected through a 1-5 Likert scale questionnaire, and then tabulated using statistical analysis with the SPSS computer program. The collected data will be analyzed in several stages, the first stage is testing the validity and reliability of the research instruments, testing classical assumptions, and finally multiple linear regression analysis. The research results show that work motivation does not significantly influence employee performance, organizational culture has a positive and significant influence on employee performance, and work discipline has a positive and significant influence on employee performance. The results of this research prove that the variables of work motivation, organizational culture and work discipline simultaneously influence the performance of PT employees. Pelindo Regional 2 Cirebon, and its influence is positive. Employees who have good performance can make a significant contribution to achieving company goals. They will help increase productivity, innovation and customer satisfaction.